2020
DOI: 10.1097/mao.0000000000002621
|View full text |Cite
|
Sign up to set email alerts
|

Can Benign Paroxysmal Positional Vertigo Be Treated in a One Session?

Abstract: Objective: To determine the reliability and safety of posterior canal BPPV (pc-BPPV) treatment with subsequent assessment of the effectiveness of the maneuver in a single session, compared to the classic weekly procedure. Method: A prospective study of two randomized groups of unilateral pc-BPPV was performed: a weekly management group (27 patients) and single-session treatment group (26 patients). The number of maneuvers required to clear pc-BPPV, inci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…In most cases, its characteristics can easily be interpreted as excitation/inhibition of ampullary vestibular receptors, followed by the inappropriate flow of endolymph associated with abnormal otoconia in semicircular canals [ 3 ]. The most common cause of BPPV is tubular stones in posterior canal (PC) and lateral semicircular canals (LC), and treatment is a physical operation that removes (repositions) the auricle from the canal [ 7 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In most cases, its characteristics can easily be interpreted as excitation/inhibition of ampullary vestibular receptors, followed by the inappropriate flow of endolymph associated with abnormal otoconia in semicircular canals [ 3 ]. The most common cause of BPPV is tubular stones in posterior canal (PC) and lateral semicircular canals (LC), and treatment is a physical operation that removes (repositions) the auricle from the canal [ 7 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is strong evidence that the Epley maneuver is effective and safe in the treatment of PC-BPPV ( Hilton and Pinder, 2014 ). Varying results from different studies have raised questions about which is the best EM protocol ( Dorigueto et al., 2005 ; Korn et al., 2007 ; Perez-Guillen et al., 2020 ). Our goal in this study was to examine more closely the short-term therapeutic effect of two EM protocols in the demanding environment of the emergency department.…”
Section: Discussionmentioning
confidence: 99%
“…Third, as shown in the video, short interval time was set aside between repositioning and diagnostic maneuvers, which should be associated with the occurrence of CS or reentry in the reported case. Although repeated repositioning and diagnostic maneuvers within the same session is considered as a safe and effective approach to the management of BPPV, with a low risk of CS (15,16), enough interval between maneuvers should set aside to avoid the occurrence of CS or re-entry conditions (12–14). There is not yet a consensus on interval time between maneuvers (15), a study suggested that at least a 15-minitus interval time between maneuvers should be kept out, which may decrease the incidence of CS or re-entry (14).…”
mentioning
confidence: 99%